2023
DOI: 10.1038/s41598-022-26557-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cardiotoxicity and plasma ropivacaine concentrations after serratus intercostal fascial plane block in an experimental model

Abstract: Serratus intercostal fascial plane block (SIFPB) has emerged as an alternative to paravertebral block in breast surgery. It involves the administration of high volumes and doses of local anesthetics (LA) that can potentially reach toxic levels. Ropivacaine is widely used in thoraco-fascial blocks; however, there is no information on the plasma concentrations attained after SIPFB and whether they are associated with cardiotoxicity. Plasma concentrations of ropivacaine and its electrophysiological effects were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Other trials observed that total venous ropivacaine concentration increased from 2.39 to 6.08 µg/mL during long-term epidural ropivacaine infusion, and even a value of 7.1 µg/mL was reported with no evidence of systemic toxicity events [14,15]. An experimental animal model draws a similar conclusion that it is not related to adverse electrophysiological or hemodynamic effects when ropivacaine concentration reaches potentially toxic levels [16]. In some cases, it is difficult to justify the correlation between local anesthetic concentrations and signs of systemic toxicity.…”
Section: Discussionmentioning
confidence: 86%
“…Other trials observed that total venous ropivacaine concentration increased from 2.39 to 6.08 µg/mL during long-term epidural ropivacaine infusion, and even a value of 7.1 µg/mL was reported with no evidence of systemic toxicity events [14,15]. An experimental animal model draws a similar conclusion that it is not related to adverse electrophysiological or hemodynamic effects when ropivacaine concentration reaches potentially toxic levels [16]. In some cases, it is difficult to justify the correlation between local anesthetic concentrations and signs of systemic toxicity.…”
Section: Discussionmentioning
confidence: 86%